Scriptotherapy and the Working Through Traumatic Experiences in Doris Lessing’s The Golden Notebook (1962) - Bagahayou ,Nour Elhouda; Bendjedia,Soumia; BENTAHER, Soumia (Faculty of Letters and Foreign Languages Department of English, 2019)
The current dissertation offers a new critical reading of Doris Lessing’s The Golden Notebook that takes up themes of trauma and healing as quintessential tropes to understand her approach to and representation of female traumatic experiences. The research also aims at demonstrating how Lessing’s novel can be read as a narrative of healing or scriptotherapy. Moreover, this dissertation seeks to highlight the significance and symbolism of the central female character, Anna Wulf, in rendering its creator’s vision about a traumatized subject which uses scriptotherapy as a means to work through a traumatic experience. Through her fiction, we assume that Lessing demonstrates the transformative power of trauma narratives and their capacity to turn unspeakable stories about women’s suffering into narratives of testimony that are infused by the power of healing. Then healing narratives, according to Lessing, constitute an adequate tool for the representation, transmission, and healing of female traumas. So, in her feminist approach to trauma, Doris Lessing attempts to invest in therapeutic and healing discourses that identify her female character’s story as a form of scriptotherapy.